Meta-research on the field of studies on educational inclusion policies in Argentina (2003-2021) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
This paper presents the results of an inquiry — from a meta-research approach— on the production of knowledge about educational inclusion policies for the secondary school in Argentina between 2003 and 2021. The study covers a set of 39 papers published in scientific journals by scholars of Argentine institutions. Our analysis is focused, in the first instance, on the theoretical and methodological approaches and in the spaces of knowledge production. Secondly, we make an approach to the supranational dimension of the political agenda, understanding that the "problem" of educational inclusion is part of a global educational reform agenda. Our main goal is to contribute to the understanding of the functioning of the field of educational policy research in Argentina from an epistemological lens.Palabras clave: Educational inclusion. Inclusive education. Educational policy. Meta-research - Secondary school.